2013
DOI: 10.3892/or.2013.2466
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of prophylactic closure for a large mucosal defect after colorectal endoscopic submucosal dissection

Abstract: Endoscopic submucosal dissection (ESD) is not a common treatment for colorectal neoplasms because of its technical difficulties and has a higher incidence of complication. In particular, perforation is one of the severe complications and these patients require surgical intervention. However, whether prophylactic closure after colorectal ESD prevents perforation and other complications is not known. In the present study, we assessed the efficacy and safety of prophylactic closure for a large mucosal defect afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 32 publications
4
65
1
Order By: Relevance
“…Frequent use of electrocautery with an electrosurgical knife due to submucosal fibrosis could cause excessive heating of the muscular layer, and transmural burn syndrome may be more likely to occur in patients with fibrosis than in those without fibrosis. Previous retrospective studies have reported that PCC of mucosal defects after EMR and ESD significantly decreased the frequency of AEs, such as fever and abdominal pain [14,15]. In this study, although the resected specimen size and circumference of ESD ulcers in the group with complete PCC had a tendency to be smaller than those in the group with incomplete PCC, univariate analysis of AEs in this study likewise found the frequency of AEs to be higher in the group with incomplete PCC.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Frequent use of electrocautery with an electrosurgical knife due to submucosal fibrosis could cause excessive heating of the muscular layer, and transmural burn syndrome may be more likely to occur in patients with fibrosis than in those without fibrosis. Previous retrospective studies have reported that PCC of mucosal defects after EMR and ESD significantly decreased the frequency of AEs, such as fever and abdominal pain [14,15]. In this study, although the resected specimen size and circumference of ESD ulcers in the group with complete PCC had a tendency to be smaller than those in the group with incomplete PCC, univariate analysis of AEs in this study likewise found the frequency of AEs to be higher in the group with incomplete PCC.…”
Section: Discussionsupporting
confidence: 55%
“…No AEs (n = 182) P value Regarding to delayed bleeding, reportedly, PCC after EMR or ESD decreases it [14,15]. However, in this study, no significant difference was observed in the frequency of delayed bleeding in the subgroup analysis of resected specimen size of < 40 mm between the group with complete PCC and the group with incomplete PCC.…”
Section: Aes (N = 29)contrasting
confidence: 56%
“…To avoid such delayed adverse events, prophylactic complete closure of the mucosal defect after C-ESD has been attempted by some operators, and the possibility that it may decrease delayed adverse events has been reported [6][7][8][9][10][11]. Conventional clip closure has been used most frequently and is an effective technique, but the size of the mucosal defect is limited, resulting in incomplete closure in several cases [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional clip closure has been used most frequently and is an effective technique, but the size of the mucosal defect is limited, resulting in incomplete closure in several cases [6][7][8]. Especially, mucosal defects of > 40 mm tended to have incomplete closure [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although several reports have suggested that the inflammation after endoscopic submucosal dissection (ESD) of the colon can be reduced by closure of the ulcer [1,2], a simpler and more reliable closure has not been reported for ulcers over 6 cm in diameter.…”
mentioning
confidence: 99%